An introduction to the theoretical foundations of Islamic transactions - Saleem, Muhammad Yusuf (Ilmiah Publishers, 2009)
The book presents a study of the theoretical foundations for Islamic transactions. It provides the reader with a solid background which is essential for a comprehensive knowledge Islamic transactions, banking and finance. The main discussion include the sources for Islamic commercial and financial laws, the objectives of Sharia'ah with regard to commercial and financial transactions, property and its classifications and their implications for transactions, rights and financial rights, ownership and its types, the theory of contract, the pillars of contract, its classifications, and its options. The last chapter discusses factors that invalidate transactions such as usury/interest (riba), ambiguity (gharar), gambling (maysir), and the involvement of prohibited properties. The book is as important text note only for the students but also for all those who work in Islamic banks and financial institutions.